2002
DOI: 10.1111/1467-8624.00484
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Change in Inhibited and Uninhibited Children

Abstract: After screening 368 toddlers and selecting 77 into extremely inhibited, extremely uninhibited, and intermediate groups, 63 children (82%) were followed up at 4 and 7 years. Minority subgroups of both the inhibited and uninhibited children showed continuity on outcomes consisting of questionnaire measures of shyness, inhibitory control, and impulsivity, as well as multiepisode observational measures of behavioral inhibition and exuberance. Change from both inhibited and uninhibited status from the toddler age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
145
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 37 publications
9
145
2
1
Order By: Relevance
“…While researchers have reported statistically significant associations among laboratory measures of temperament both within the same assessment period and over time, generally speaking the magnitude of these associations, when present, are modest, particularly when extreme groups are not the focus of investigation (Kagan et al, 1987;Pfeifer, Goldsmith, Davidson, & Rickman, 2002;Reznick et al, 1986;Rothbart, 1988). Indeed, in the present study we found no correlation between fearful responses to Stranger Approach and to the Risk Room.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…While researchers have reported statistically significant associations among laboratory measures of temperament both within the same assessment period and over time, generally speaking the magnitude of these associations, when present, are modest, particularly when extreme groups are not the focus of investigation (Kagan et al, 1987;Pfeifer, Goldsmith, Davidson, & Rickman, 2002;Reznick et al, 1986;Rothbart, 1988). Indeed, in the present study we found no correlation between fearful responses to Stranger Approach and to the Risk Room.…”
Section: Discussioncontrasting
confidence: 79%
“…Kagan among others has argued the value of studying extreme groups, particularly when trying to understand the role of biological processes in temperament (Kagan, Snidman, & Arcus, 1998). In most cases, extreme groups are followed and subsequent measures of fearful behavior and physiological reactivity are examined to determine if the groups still differ in fearful temperament (e.g., Kagan et al, 1987;Pfeifer et al, 2002). In the present study, we grouped children according to the consistency of their fearful behavior across contexts and informants, and then re-examined the associations we had already examined for the group as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The twelve episodes were designed to elicit different behaviors and emotions. The episodes in the Lab-TAB were drawn from previous studies that examine a number of research questions related to child development and emotionality (e.g., Kochanska & Knaack, 2003;Pfeifer et al, 2002). The children returned to a neutral state in between each episode by taking a short play break.…”
Section: Assessment Proceduresmentioning
confidence: 99%
“…Specifically, low PA and high BI share the common feature of low behavioral approach/ engagement (Durbin, Klein, Hayden, Buckley, & Moerk, 2005;Pfeifer, Goldsmith, Davidson, & Rickman, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation